2004
DOI: 10.1080/02724980343000396
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic structure and deaf spelling errors: Syllables, letter frequency, and speech

Abstract: Syllable structure influences hearing students' reading and spelling (e.g., Badecker, 1996; Caramazza & Miceli, 1990; Prinzmetal, Treiman, & Rho, 1986; Rapp, 1992; Treiman & Zukowski, 1988). This may seem unsurprising since hearers closely associate written and spoken words. We analysed a corpus of spelling errors made by deaf students. They would have learned English orthography with an attenuated experience of speech. We found that the majority of their errors were phonologically implausible but orthographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…the frequency of occurrence of two adjacent letters) were a less accurate measure than syllable boundaries in Olson and Nickerson's (2001) data. Their results were confirmed by the spelling errors of deaf individuals (Olson & Caramazza, 2004). Although the general error pattern differed from a hearing control group (the deaf made substantially less phonologically plausible errors), the great majority of errors were orthographically legal.…”
Section: Phonological Awareness and Written Language In The Deafmentioning
confidence: 53%
See 1 more Smart Citation
“…the frequency of occurrence of two adjacent letters) were a less accurate measure than syllable boundaries in Olson and Nickerson's (2001) data. Their results were confirmed by the spelling errors of deaf individuals (Olson & Caramazza, 2004). Although the general error pattern differed from a hearing control group (the deaf made substantially less phonologically plausible errors), the great majority of errors were orthographically legal.…”
Section: Phonological Awareness and Written Language In The Deafmentioning
confidence: 53%
“…Due to the two groups' different experiences with spoken language, similar patterns of performance for the two groups would suggest that the effect must not be one based on spoken language. Instead, identical syllabic effects must have their origin in abstract principles of organisation, as postulated by the hypothesis of orthographic autonomy (Badecker, 1996;Olson & Caramazza, 2004;Olson & Nickerson, 2001).…”
Section: Syllabic Structures In Typingmentioning
confidence: 98%
“…This visuographemic strategy has been observed in deaf people on several occasions, for the spelling of isolated words (Padden, 1993;Burden & Campbell, 1994). A number of studies have also sought to explain the structure and nature of the resulting graphemic errors (Hanson et al, 1983;Olson & Caramazza, 2004). Here, our main findings were that (i) this type of error also occurs during the more ecological activity of composing a descriptive text and (ii) recourse to the underlying visuographemic strategy depends on the visuospatial capacities of working memory.…”
Section: Discussionmentioning
confidence: 76%
“…The inability to hear an acoustically based language reduces the phonological cues that are usually used to detect the acoustic consequences of graphemic confusions (cf. results recorded by Dodd, 1980;Padden, 1993;Hanson, Shankweiler, & Fischer, 1983;Olson & Caramazza, 2004). This reduced phonological awareness and its negative impact on spelling are not, however, definitive; being determined by age, literacy level and probably also the intrinsic regularity of the relevant language.…”
Section: Theoretical Frameworkmentioning
confidence: 68%
“…Buchwald & Rapp, 2006;Schwartz, Wilshire, Gagnon, & Polansky, 2004;Caramazza, Papagno, & Ruml, 2000;Ward & Romani, 1998b;Gagnon & Schwartz, 1997;Kay & Hanley, 1991;Neils, Roeltgen, & Greer, 1995; Serial position data 4 Papagno & Girelli, 2005;Cipolotti, Bird, Glasspool, & Shallice, 2004;Buchwald & Rapp, 2004;Cotelli, Abutalebi, Zorzi, & Cappa, 2003;Croisile & Hibert, 1998). Recently, Mactynger and Shallice (2009) showed that there are some systematic distortions of the serial position curve that the Wing and Baddeley method can introduce (see also accompanying response Wing & Baddeley, 2009), and they suggested an alternative method that we have also used and in a study of spelling errors made by deaf participants, and speech errors made by aphasic patients (Olson, 1995;Olson & Caramazza, 1999).…”
mentioning
confidence: 99%